Maxillary Anterior Teeth Proportions for Creating Esthetically Pleasuring Smile in Nepalese Patients - Rokaya, Dinesh; Humagain, Manoj; Amornvit, Pokpong (Journal of Nepal Health Research Council, 2018)
N/A